Investigating the Implementation of Language Learning Strategies in Alleviating Foreign Language Anxiety Among University Students - Hasan, Muhammad; Masruroh, Lu'luil (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2024)
Foreign Language Anxiety (FLA) significantly impacts language acquisition, yet its interplay with Language Learning Strategies (LLS) remains underexplored in the context of Arabic language learning in Indonesian Islamic higher education. This study examines the relationship between FLA and LLS among university students learning Arabic at STAI Al-Yasini Pasuruan, Indonesia. In this setting, cultural and religious factors may uniquely influence language anxiety. The research aims to assess the levels of FLA, evaluate the frequency of LLS use, and explore the correlation between these variables. Employing a quantitative descriptive and correlational design, data were collected using Horwitz and Cope’s Foreign Language Classroom Anxiety Scale (FLCAS) and Oxford’s Strategy Inventory for Language Learning (SILL). The study involved 82 students, selected through convenience sampling due to its practicality and accessibility within the institution’s academic schedule. Descriptive statistics revealed moderate anxiety levels among participants, with female students reporting slightly higher anxiety than males. Students moderately used most LLS categories but employed compensation strategies less frequently. Pearson product-moment correlation analysis indicated a statistically significant negative correlation (r = -.140, p < .05) between FLA and LLS, suggesting that increased use of LLS is associated with reduced anxiety in Arabic language learning. These findings offer practical implications for educators integrating strategy training to mitigate FLA, particularly in culturally distinct educational contexts.